THE EFFECT OF ACCOUNTABILITY ON EMPLOYEE PERFORMANCE IN GOVERNMENT AGENCIES - Meti Mediyastuti sofyan (Journal of Public Administration, 2023)
Improving the performance accountability of government agencies is one of the important challenges faced in the era of demands for quality public services. The Bandung Regency Government as one of the regions in Indonesia also faces similar challenges. Therefore, this study aims to analyze the performance accountability of government agencies in the Bandung Regency Government. Researchers used quantitative research. Research Subject The research subject is a line or research boundary that is useful for researchers in determining objects or people as the point of attachment of research variables. Bandung Regency Civil Service Police Unit Office. Regional Technical Institutions The determination of the sample was carried out based on consideration of the significance of the agency in the delivery of public services and the representativeness of various government sectors. In selecting the sample, it is also necessary to consider the variation in the size of agencies as well as the diversity of their functions and responsibilities to cover various aspects of relevant public services. The results showed that the condition of performance accountability of government agencies in the Bandung Regency Government still needs to be improved. Factors that influence performance accountability include good leadership and management, effective internal control systems, public participation in supervision, and financial transparency and accountability.